2021
DOI: 10.1088/1755-1315/904/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Performance and F1 Crosses For Several Bread Wheat Cultivars Under Varying Levels of Nitrogen Fertilization

Abstract: Six bread wheat varieties representing different traits were crossed in a half-diallel in 2017/2018 season. The 6 parents and its 15 F1 crosses were evaluated under normal and N-stress conditions in 2018/2019 season, to study the mean performance and the combining ability for earliness and morpho-physiological traits and biomass yield of wheat under normal and N-stress conditions. Mean squares of genotypes, parents, crosses, and parents versus crosses were significant or highly significant for most of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Hence, to achieve each agronomic and environmental aims we need to manage the nitrogen fertilization in agricultural process and determine the optimal nitrogen levels (El-Sorady et al 2022). Abdel-Moneam et al (2021) investigate that the best biomass yield /plant was in the cultivar Shandweel-1 at normal condition and Saad et al (2022) reported that Gemaiza 11 recorded highest biomass, straw yield values and plant height compared to Misr1 which displayed higher levels of seed index.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, to achieve each agronomic and environmental aims we need to manage the nitrogen fertilization in agricultural process and determine the optimal nitrogen levels (El-Sorady et al 2022). Abdel-Moneam et al (2021) investigate that the best biomass yield /plant was in the cultivar Shandweel-1 at normal condition and Saad et al (2022) reported that Gemaiza 11 recorded highest biomass, straw yield values and plant height compared to Misr1 which displayed higher levels of seed index.…”
Section: Introductionmentioning
confidence: 99%